Nutrtional Quality of Fermented Spray Dried Medida Formulated From Malted Brown Rice with Bifidobacterium Longum BB 536 - Mohammed Kabeir, Barka (2004)
The processing technique of medida, the traditional Sudanese porridge was modified to improve the nutritional quality. The paddy rice was steeped and malted at 30 ˚C. Medida was formulated using 225 g brown rice flour of two days malted paddy with added skim milk at 2.25 %, 4.5% and 10% levels (W/V) were studied. The initial pH was 6.7 and fermentation was run to a final pH of 4.4 using culture of Bifidobacterium longum BB 536. Fermented Medida containing B. longum BB 536 cell counts up 9 Log CFU/ ml was spray dried at different heat adaptations and spray drying air outlet temperatures with fixed inlet temperature of 160 ˚C. Two days malted rice flour had the highest protein (9.16 ± 0.16 %) and lysine (7.70 ± 0.10 %) content, in addition to the significant (P< 0.01) increase in glucose (8.67 ± 0.07) due to the activity of alpha amylase enzyme. The total solid of the malted brown flour was high, 3.4 folds at the similar viscosity of the brown flour. During fermentation of medida the highest count of 9.82 ± 0.18 log CFU B. longum BB 536/ ml was obtained with 10 % of added skim milk. At this level, the final concentrations of lactic and acetic acids were 57.76 ± 0.78 and 6.07 ± 0.15 μmol / ml, respectively. The relative ratio of acetic acid to lactic acid decreased as fermentation continues due to the higher rate of lactic acid production. Under refrigerated storage the count of B. longum BB 536 remained relatively stable during the first week (9.7 ± 0.1log CFU / ml), then decreased by 0.9 log CFU / ml in the second week. At stable flowing characteristics and a similar viscosity of spontaneously fermented brown rice medida, there was 12 folds increase in total solids, the protein and energy density were significantly (P< 0.01) improved. The essential amino acids including lysine and methionine were highly augmented. The survival of B. longum BB 536 during the spray drying of the fermented medida decreased with elevation of outlet temperature, but increased dependent on heat adaptation temperature prior to the spray drying. At adaptation temperature of 45 ˚C for 25 min, there was a significant improve in viability retention at 85 – 88 ˚C outlet temperature, and spray dried medida with 7.81 ± 0.1 Log CFU B. longum BB 536/ g was obtained. Under refrigerated storage the viable count of the strain (7.81 ± 0.1 Log CFU / g) remained stable for 11 days, and then decreased by 0.77 log CFU/ g in 70 days. Compared with commercial cereal based food, the nutritional composition of the spray dried fermented medida is better. Referring to the recommended dietary allowance for 1- 12 years old, 475 g spray dried medida provides more than the sufficient protein (92 g) and energy (1767 kcal) requirements. The same amount provides the whole needs from calcium (642 mg) and the essential amino acids as follow: 1232 mg lysine, 2028 mg valine, 874 mg isoleucine, 1206 mg lucine, and 796 mg thronine. In conclusion, two days malted brown rice flour is nutritionally superior in the protein and the limiting amino acid lysine with having higher total solids. Moreover, the fermented medida from malted rice is a suitable food system for the delivery of B. longum BB 536. The addition of 10% skim improved the growth of B. longum BB 536 and the quality of medida from malted rice. The heat adaptation prior to the spray drying potentially improved the survival of B. longum BB 536, and the viable count attained in the final powder met the number required to presence in the probiotic bifidus product. Hence, the spray dried medida from malted brown rice is of dietetic-therapeutic benefit.